RelA Is an Essential Target for Enhancing Cellular Responses to the DNA Repair/Ref-1 Redox Signaling Protein and Restoring Perturbated Cellular Redox Homeostasis in Mouse PDAC Cells - Mijit, Mahmut; Wireman, Randall; Armstrong, Lee; Gampala, Silpa; Hassan, Zonera; Schneeweis, Christian; Schneider, Guenter; Zhang, Chi; Fishel, Melissa L.; Kelley, Mark R. (Frontiers in Oncology, 2022)
Pancreatic ductal adenocarcinoma (PDAC) is one of the deadliest cancers with a poor response to current treatment regimens. The multifunctional DNA repair-redox signaling protein Ref-1 has a redox signaling function that activates several transcriptional factors (TFs) including NF-B (RelA), STAT3, AP-1. These have been implicated in signaling in PDAC and associated with cancer progression and therapy resistance. Numerous studies have shown a role for RelA in PDAC inflammatory responses and therapy resistance, little is known as to how these inflammatory responses are modulated through Ref-1 redox signaling pathways during pancreatic pathogenesis. RelA and STAT3 are two of the major targets of Ref-1 and are important in PDAC pathogenesis. To decipher the mechanistic role of RelA in response to Ref-1 inhibition, we used PDAC cells (KC3590) from a genetically engineered KrasG12D-driven mouse model that also is functionally deficient for RelA (Parent/Vector) or KC3590 cells with fully functional RelA added back (clone 13; C13). We demonstrated that RelA deficient cells are more resistant to Ref-1 redox inhibitors, APX3330, APX2009, and APX2014, and their sensitivity is restored in the RelA proficient cells. Knockdown of STAT3 did not change cellular sensitivity to Ref-1 redox inhibitors in either cell type. Gene expression analysis demonstrated that Ref-1 inhibitors significantly decreased IL-8, FOSB, and c-Jun when functional RelA is present. We also demonstrated that PRDX1, a known Ref-1 redox modulator, contributes to Ref-1 inhibitor cellular response. Knockdown of PRDX1 when functional RelA is present resulted in dramatically increased PDAC killing in response to Ref-1 inhibitors. The enhanced cell killing was not due to increased intracellular ROS production. Although Ref-1 inhibition decreased the NADP/NADPH ratio in the cells, the addition of PRDX1 knockdown did not further this redox imbalance. This data suggests that the mechanism of cell killing following Ref-1 inhibition is at least partially mediated through RelA and not STAT3. Further imbalancing of the redox signaling through disruption of the PRDX1-Ref-1 interaction may have therapeutic implications. Our data further support a pivotal role of RelA in mediating Ref-1 redox signaling in PDAC cells with the KrasG12D genotype and provide novel therapeutic strategies to combat PDAC drug resistance.